Sea temperature is the primary driver of recent and predicted fish community structure across Northeast Atlantic shelf seas. Issue 9 (10th March 2023) - Rutterford, Louise A.; Simpson, Stephen D.; Bogstad, Bjarte; Devine, Jennifer A.; Genner, Martin J.
Abstract: Climate change has strongly influenced the distribution and abundance of marine fish species, leading to concern about effects of future climate on commercially harvested stocks. Understanding the key drivers of large‐scale spatial variation across present‐day marine assemblages enables predictions of future change. Here we present a unique analysis of standardised abundance data for 198 marine fish species from across the Northeast Atlantic collected by 23 surveys and 31, 502 sampling events between 2005 and 2018. Our analyses of the spatially comprehensive standardised data identified temperature as the key driver of fish community structure across the region, followed by salinity and depth. We employed these key environmental variables to model how climate change will affect both the distributions of individual species and local community structure for the years 2050 and 2100 under multiple emissions scenarios. Our results consistently indicate that projected climate change will lead to shifts in species communities across the entire region. Overall, the greatest community‐level changes are predicted at locations with greater warming, with the most pronounced effects at higher latitudes. Based on these results, we suggest that future climate‐driven warming will lead to widespread changes in opportunities for commercial fisheries across the region. Abstract : We present a unique analysis of standardised abundance data for 198 marine fish species, reaching across the Northeast Atlantic from northern Norway to southern Portugal. The data were collected by 23 fisheries surveys between 2005 and 2018. The study clearly identifies sea temperature as the primary driver of fish community composition. The analysis implies that fisheries at higher latitudes, within the study area, will be most impacted by further climate change. In turn, future climate‐driven warming could lead to widespread changes in opportunities for commercial fisheries across the region.